Transport Across Natural and Modified Biological Membranes and its Implications in Physiology and Therapy - Kulbacka, Julita; Satkauskas, Saulius (Advances in Anatomy, Embryology and Cell Biology,, 2017)
This book elucidates the mechanisms involved in biological membrane functions. It describes the new modalities and characterization for basic in vitro as well as computer models of biological membranes. Biological membranes are analyzed in terms of advances in molecular dynamics. The individual chapters provide an in depth analysis of images from various biological models. The potential of membrane models in the context of treatment trials is discussed. The authors present new insights and current concepts for treatment procedures (nanocarriers, electroporation, channel blockers).